PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA UD. PROBO SAKTI PROBOLINGGO - M. Saiful Bahri; Agustina Puji; Tumini -; Agung Wicaksono (Universitas Bina Taruna Gorontalo, 2023)
Research objectives at UD. Probosakti Probolinggo is to examine how the causal relationship between leadership, work discipline and motivation on employee performance. This research is a causal association type, with a saturated sampling method. The sample is 31 employees from the entire population of 31 employees. Using SPSS as an analytical tool produces a value of Fcount > Ftable (25.341 > 2.96) with a significance of 0.000 <0.05. This proves that leadership, discipline and motivational factors have a joint and significant effect on employee performance. Likewise, the calculated t value of the leadership, discipline and motivation variables > from the t table value with a confidence level of <0.05, meaning that each independent variable has an influence on employee performance. Meanwhile, 70.9% of the fluctuations in performance were contributed by leadership, discipline and motivation, and 29.1% of variations in performance fluctuations were contributed by variables outside the study, and the greatest influence on variations in performance fluctuations was influenced by work motivation with an influence value of 0.505.